Bridging the nexus between Fintech, operational efficiency and banks profitability: the moderating role of bank size - Asmaa Hamdy Abdelaziz Mohamed Elmahdy; Menna Talla Khaled Mohamed Abdelkader; Mina Ayman Mikhaeel Shaker (Future Business Journal)
Abstract Purpose The current research investigates the nexus between investments in financial technology (Fintech) and banks’ profitability. It also examines whether banks’ operational efficiency (OE) as a mediator and the bank size (BS) as a moderator can impact their profitability in digital transformation. Design/methodology/approach The Generalized method of moments (GMM) model is employed to construct estimators for 16 banks operating in Egypt from 2015 to 2022. Findings The empirical analysis reveals a significant and negative association between Fintech applications and banks’ profitability in Egypt. This can be attributed to the substantial expenses associated with digitalization as well as the influence of the challenging macroeconomic conditions. The results of our research provide evidence that operational efficiency mediates the nexus between Fintech and profitability. Furthermore, research has revealed that bank size does not moderate the impact of Fintech on profitability. However, due to higher earnings volatility bank size has a significant and negative association with banks’ profitability. Research implications Our research has important policy implications as we propose that while there is currently a negative association between the implementation of Fintech and banks’ profitability, banks are expected to achieve higher profitability in the future by increasing investment in Fintech. Originality/value Given the limited amount of existing research on Fintech applications in developing countries, this research intends to contribute to the existing literature by examining the mediating and moderating effects of a bank’s OE and BS on the association between Fintech and the profitability of banks operating in Egypt. Accordingly, this research highlights this nexus, which may have substantial implications for resolving the struggles experienced by the banks operating in Egypt after the crucial incidents it faced, which, in turn, affected the financial stability of the whole economy.